PERANCANGAN VISUAL BRANDING IDENTITY ANAK HIU CLOTHING PADANG - AULIA RIDHA, Ir. Drs. Heldi, M.Si. Ph.D., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Anak Hiu Clothing is a distribution outlet that was pioneered by the Boy Agung since 2008 has grown until now as the needs and interests of high society against one surf brand products. However, Anak Hiu Clothing do not have a fixed visual identity branding image and identity as a differentiator from competitors. Destination branding visual identity design Anak Hiu Clothing is to establish brand awareness and market segmentation in the community of the uniqueness and advantages through the process of branding visual identity.The analytical method used in the design of visual identity branding Anak Hiu Clothing approach SWOT analysis (Strength, Weakness, Opportunity, Threat). The the idea development orientation of designing visual identity branding includes the main media in the form of logos and media support in the form of T-shirts, tote bags, sales invoices, hang tags, stamps, cards, stickers, pens and neon box. Hopefully, by the visual design identity branding can provide a meaningful contribution through positioning, in addition to strengthening the competitiveness of the competitors distro clothing that has been developed at this time.Keywords: Visual Branding, Branding, Identity, Design, Anak Hiu Clothing.